A young Lady with Secondary Tuberculosis of Breast - Islam, A; Gafur, MA; Khan, SA; Karim, MR; Mohiuddin, M; Jahan, S (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):618-21 The abstract of this article is available on the PubMed website